Balloon-Occluded Retrograde Transvenous Obliteration (BRTO): A Novel Method of Obliterating Gastric Varices. Report of Six Cases and Review of Literature - Thapa, Ajit; Koirala, Dinesh; Pathak, Rahul; Chataut, Dinesh; Sharma, Sashi; Bhandari, Brindeswari Kafle; Jha, Anurag; Hamal, Rabin; Pandey, Rajesh; Gyawali, Arun; Bhusal, Mohan (Journal of Advances in Internal Medicine, 2020)
Portal hypertension results in various complications, gastroesophageal varices being one of them. Although less common than esophageal varices, gastric varices are difficult to obliterate and carry a higher mortality rate when bleeding occurs. They are less amenable to sclerotherapy, endoscopic variceal ligation. Balloon-Occluded Retrograde Transvenous Obliteration (BRTO) has been developed as a minimal invasive procedure to obliterate gastric varices. BRTO is an endovascular procedure where a balloon catheter is inserted into a draining vein of gastric varix, and the sclerosant can be injected into the varices through the catheter during balloon occlusion. We report six cases where BRTO was done for gastric varices obliteration.